University Technological Entrepreneurship Projects: Factors of Success - P. S. Sorokin; P. I. Egorov (Высшее образование в России)
The paper presents the results of an empirical analysis of the success factors in university technological entrepreneurial projects, based on a unique empirical dataset created with the support of the project office and the office for promoting the federal project «University Technological Entrepreneurship Platform». The dataset includes a ranking of over 1,000 university projects from 2023, each of which contains information on approximately 35 characteristics, both financial and non-financial. The success indicators selected for analysis are the «final ranking position» and «investment attractiveness of the project». Statistical methods, implemented through Python libraries, were used to examine the relationships between different forms of project support and the aforementioned characteristics. The results highlight the critical role of the university environment in supporting entrepreneurial projects, while also revealing that specific support measures can exhibit varying degrees of association with project success. Two key findings are noteworthy. First, there is no positive correlation between the project’s strong embeddedness in the university environment (e.g., a team assembled within the university or a project initially started as an academic exercise) and the project’s success. Second, among the support measures implemented within the current federal project «University Technological Entrepreneurship Platform», the strongest association with the success of entrepreneurial initiatives is found in participation in startup studios. Considering contemporary discussions on the need to seek new solutions to enhance the educational and life experiences of modern students, bringing them closer to the realities of a dynamically changing labor market, the university startup studio model may serve as a source for developing new models of university organization.